Efforts to Improve Learning Outcomes of Basketball Dribbling Through a Play Approach - Riyo Saputra; Zainal Widyanto; Rio Wakhid Hujjatul Islam (Tinta Emas Publisher, 2023)
This study aims to improve learning outcomes of dribbling through a play approach in class VIII students of SMP Negeri 2 Jayapura. The method used is class action research (PTK). This research consists of two cycles, each cycle consists of two meetings. The subjects in this study were 8D class students of SMP Negeri 2 Jayapura totaling 37 students consisting of 20 male students and 17 female students. The data analysis technique used descriptive statistics with the percentage formula. The results showed that there was an increase in learning outcomes of basketball dribbling through the play approach in class 8D students of SMP Negeri 2 Jayapura, with learning completeness in cycle I of 59.46% (22 children out of 37) and increased in cycle II of 83.78% (31 children out of 37). Based on these results it can be concluded that there is an increase in learning outcomes of dribbling through the playing approach in class 8D students of SMP Negeri 2 Jayapura